THE TRANSITION PROCESS FROM THE 2013 CURRICULUM (K13) TO THE MERDEKA CURRICULUM IN LEARNING AT MTS AL-WASHLIYAH TEMBUNG - Ayundari, Nanjah Fachira; Rustam, Rustam (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
This study explores the transition process from the 2013 Curriculum (K13) to the Merdeka Curriculum at MTs Al-Washliyah Tembung, an educational reform aimed at promoting student-centered learning and character development through Pancasila values. The purpose of this research is to analyze how the transition was implemented, identify challenges faced during the process, and assess the school's readiness and sustainability efforts in adopting the new curriculum. A qualitative case study approach was used, involving interviews with key stakeholders, field observations, and document analysis. The findings indicate that while initial efforts such as training and curriculum socialization were conducted, they lacked optimal documentation and consistency. Teachers have started to adopt new methods, including diagnostic assessments and Pancasila Student Profile (P5) projects, but the implementation remains inconsistent due to limited resources and guidance. Standardization efforts are present but remain informal, with no written SOPs in place. The study concludes that the transition is still in the "changing" phase of Lewin's Change Management Model and highlights the need for systematic strategies, structured training, and comprehensive documentation to ensure long-term curriculum sustainability and improved educational quality.